KATA â€œALLAHâ€ DALAM AL-QURAN DAN ALKITAB Kajian Terhadap Pelarangan Menggunakan Kata â€œAllahâ€ Bagi Selain Muslim - Arifin, Zainal (Jurnal THEOLOGIA, 2014)
Abstract: This study appears due MUIS Malaysia ban the use of the word "Allah" for the citizens is not Islam. This study examined for the purposes of the establishment of religious tolerance based on the understanding of religion. This paper seeks to explain that the word "Allah" contained in the Qur'an and the Bible, by limiting the study of the Qur’an and the Bible, to formulate the concept of "Allah" who became God for Muslims. This study found that the word "Allah" though not derived from Arabic, he eventually became part of the Arabic language of the Koran. He also became the name of God for Muslims. Furthermore, the authors found that in addition to Muslims, Christians and Jews may use the word "Allah" to indicate their God. When a Christian used to indicate the name of Jesus, it is also allowed as a form of tolerance. As the infidels Quraish mention sculpture as a means of worshiping God. Abstrak: Kajian ini muncul akibat pelarangan MUIS Malaysia dalam penggunaan kata "Allah" bagi warga bukan Islam. Kajian ini dikaji untuk keperluan tegaknya toleransi beragama berdasarkan pe¬mahaman agama. Tulisan ini berupaya menjelaskan bahwa kata "Allah" tertuang dalam Al-Quran dan Alkitab, dengan membatasi telaah pada Al-Quran dan Alkitab, merumuskan konsep "Allah" yang menjadi Tuhan bagi Muslim. Penelitian ini menemukan bahwa kata "Allah" walau bukan berasal dari bahasa Arab, ia akhirnya menjadi bagian dari bahasa Quran yang Arab. Ia juga menjadi nama Tuhan bagi umat Islam. Lebih jauh lagi, penulis menemukan bahwa selain Muslim, umat Nasrani dan Yahudi boleh menggunakan kata "Allah" untuk me-nunjukkan Tuhan mereka. Bila seorang Kristiani meng-gunakannya untuk menunjuk¬kan nama Yesus, itu juga dibolehkan sebagai wujud toleransi. Sebagaimana kaum kafir Quraisy me¬nyebutkan patung sebagai sarana me-nyembah Allah. Keywords: Allah, Al-Quran, Alkitab, God, Islam, Kristen.